Improving Students' Speaking Skill Using Mini Drama at Senior High School - Elsa Sholyhat; Nirna Nirmala (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2021)
ABSTRACT The purpose of this study determine whether there was a significant influence using Mini-drama Technique to improve students speaking skill at Tenth grade of SMKI AL KHOIRAT Tangerang in academic year 2020/2021. The method of the research used quantitative research with quasi-experimental research. In this research design consists of experimental class and control class without random selection. The students were tested by using pre-test and post-test. The result showed statistical calculation by kolmogorov-smirnova test, based on testing of hypothesis, it was known that the sig (0.000) was similar than 0.05. Therefore, it can be conclude that there is a positive effect of the mini-drama technique on students speaking skill at tenth grade of SMKI AL KHOIRAT KabupatenTangerang.